Development of a Science Literacy Instrument with a Tourism Context in Sumenep Regency in Environmental Education Lectures: Pengembangan Instrumen Literasi Sains Berkonteks Wisata Kabupaten Sumenep pada Perkuliahan Pendidikan Lingkungan Hidup - Yamin, Yamin; Nur Qomaria; Try Hartiningsih; Sardi, Pramudista; Muhamad Asyroful Ibad (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to produce a product in the form of a scientific literacy instrument in the local tourism context of Sumenep Regency during Environmental Education (PLH) lectures. This research uses research and development methods (Research & Development) using the ADDIE model which includes analysis, design, development, implementation, evaluation. The instrument used in this research was a test. The aspect measured is scientific literacy ability. The results of the question validation obtained an accumulated score with a percentage of 79.47 in the category